1968
DOI: 10.1902/jop.1968.39.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Repair Following Mucoperiosteal Flap Surgery With Full Gingival Retention

Abstract: THE DEVELOPMENT and utilization of a flap in surgery is at least four thousand years old as indicated by attempts of the early Hindus to repair facial deformities with flap surgery. Tagliacozzi is given credit for the revival of flap procedures in plastic surgery during the 16th century. These methods were later refined and employed as the mucoperiosteal flap which is widely used today in oral surgical procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
101
0
4

Year Published

1988
1988
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(108 citation statements)
references
References 7 publications
3
101
0
4
Order By: Relevance
“…The tensile strength of a mucogingival flap-tooth interface as a measure of the structural integrity of the wound has previously been investigated in animals (Hiatt et al 1968;Werfully et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The tensile strength of a mucogingival flap-tooth interface as a measure of the structural integrity of the wound has previously been investigated in animals (Hiatt et al 1968;Werfully et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Mucoperiosteal flaps with full gingival retention have been raised in Mongrel dogs (Hiatt et al 1968) and healing was histologically observed at 2 and 3 days, 1, 2 and 3 weeks and 1, 4…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They considered this a functionally acceptable repair of the dento-gingival junction since total regeneration of the original morphology failed to occur in the long epithelial attachment. Wilderman et al (1960) and Hiatt et al (1968) also reported long junctional epithelial healing following surgery in dogs. Caton and coworkers (1979Caton and coworkers ( , 1980aCaton and coworkers ( , 1980b (Bowers et al, 1985) using demineralized freeze-dried bone both with and without root submergence.…”
Section: B Periodontal Wound Healing Studiesmentioning
confidence: 90%
“…The systemic conditions include the control of periodontitis, a low total bacterial load in the mouth and cessation of smoking habits Mayfield L et al, 1998;Silvestri M et al, 2003;Tonetti M et al, 1993Tonetti M et al, , 1995Tonetti M et al, , 1996. The local conditions include the presence of space for the formation of the blood clot at the interface between the flap and the root surface (Haney JM et al, 1993;Sigurdsson TJ et al,1994; Cortellini P et al 1995; Wikesjo UME et al, 2003; Kim CS et al, 2004), the stability of the blood clot to maintain continuity with the root surface avoiding formation of a long junctional epithelium (Linghorne WJ et al, 1950;Hiatt WH et al, 1968;Wikesjo UME et al, 1990) and the soft tissue protection to avoid bacterial contamination (Selvig K et al, 1993;DeSanctis M et al, 1996;Sanz M et al, 2004).…”
Section: Introductionmentioning
confidence: 99%